Special Education Leadership In Malaysia: A Review - et. al., Zarina Osman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Special education leadership is an aspect of comprehensive management related to special education operations that includes knowledge, leadership style and also the welfare of teachers and students. Good leadership for special education programs should implement the process of planning, organizing, directing and controlling the members of the organization as well as using all organizational resources to achieve specific goals for PPKI. The leadership practiced in special education needs to make the special education program improve and be able to carry out its functions properly. This study reviews several previous articles that discuss leadership in special education. The findings of this study are hoped to be a guide to future researchers in an effort to continue the continuity of special education leadership.